A Performative Urban Intervention: displacements of a buffoon - Andre Luiz Rodrigues Ferreira (Revista Brasileira de Estudos da Presença, 2022)
The article aims to investigate the Bassibus action, created and executed by the contemporary buffoon Leo Bassi, who travels through themes and problems that affect the place of the city and its inhabitants. Action that parodies the tourist activity, Bassibus promotes with its participants a dynamic of occupation of the city and the questioning about the forces that affect it. It is concluded that this praxis of Bassi creates an artistic phenomenon that touches the political as an intersubjective process of reconfiguration of the perceptible and the thinkable, carrying a call of confrontation and resistance, both to the artist and to the spectator/participant, in the face of the capture devices and expropriation of desire.